Uncovering the Mysteries of Langerhans Cells, Inflammatory Dendritic Epidermal Cells, and Monocyte-Derived Langerhans Cell-Like Cells in the Epidermis - Otsuka, Masayuki; Egawa, Gyohei; Kabashima, Kenji (Frontiers in Immunology, 2018)
The identity of Langerhans cells (LCs) has been called into question of late due to the increasing evidence that LCs originate from macrophage lineage instead of dendritic cell (DC) lineage as previously thought. For many years, LCs have been assumed to be DCs due to its migratory capabilities. However, recent studies have demonstrated that LCs are from macrophage lineage of the adult fetal liver (FL) progenitor. Bona fide LCs are now considered tissue-resident macrophages as they originate from the FL as shown by fate mapping models. In recent years, studies have shown that there are three types of antigen-presenting cells present in the epidermis, such as LCs, monocyte-derived LC-like cells, and inflammatory dendritic epidermal cells (IDECs). Of these, LC-like cells have been characterized in both human and mouse studies, while IDECs have only been described in human studies. This has shed a new light on the area of epidermal macrophages, suggesting that there might be a misidentification and misclassification of LCs. IDECs and LC-like cells have been shown to be present in both steady state and inflammatory state, but they are present in more significant amounts under inflammatory conditions such as atopic dermatitis, ultra violet injury, and psoriasis. In this review, we discuss what is already known and discuss the possible roles of LCs, LC-like cells, and IDECs during inflammation. Most intriguingly, we discuss the possibility of LCs having a dual identity as both a macrophage and a DC. This is shown as LCs are the only tissue-resident macrophage to have shown migratory property-like DCs.